49.6k views
2 votes
4(4x - 3)=-76 Explain you solution process


User Jbgarr
by
4.5k points

1 Answer

6 votes

4(4x - 3)=-76

mutiply the bracket by 4

(4)(4x)= 16x

(4)(-3)= -12

16x-12= -76

move -12 to the other side

sign changes from -12 to +12

16x-12+12= -76+12

16x=-76+12

16x= -64

divide both sides by 16 to get x by itself

16x/16= -64/16

Cross out 16 and 16, divide by 16 and then becomes 1*1*x= x

x=-64/16

Answer: x=-4

User JoshL
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.